Efficacy, safety, and adherence of tocilizumab therapy in elderly patients with rheumatoid arthritis: A real-world observational study. (1st September 2021) - Nakao, Yoshinobu; Asanuma, Yu Funakubo; Wada, Takuma Tsuzuki; Matsuda, Mayumi; Yazawa, Hiroaki; Yoshida, Yoshihiro; Todoriki, Akira; Shintani, Ayumi; Mimura, Toshihide
Objective: We evaluated the efficacy, safety, and drug survival rate of tocilizumab in the elderly patients with rheumatoid arthritis (RA). Methods: This study was conducted in 108 RA patients who started tocilizumab between 2008 and 2018. The patients were divided into a young group (<65 years) and an elderly group (≥65 years). The efficacy, safety, and drug survival rate of tocilizumab were compared between the two groups. Results: At baseline, there were no significant differences between the elderly ( n = 45) and the young group ( n = 63) in RA duration, percentage of biologic-naïve, and RA disease activity. Health Assessment Questionnaire-Disability Index (HAQ-DI) was higher, renal function was worse, and frequency of using methotrexate was lower in the elderly group. Tocilizumab demonstrated similar efficacy in the elderly and the young group with Clinical Disease Activity Index and HAQ-DI. Compared with baseline, the frequency of steroid use was lower at one year after initiation of tocilizumab in both groups. There was no significant difference between the groups in the drug survival rate of tocilizumab for three years. Discontinuation rates of TCZ due to toxic adverse events were similar between the two groups. Conclusions: The efficacy, steroid-sparing effect, and safety of tocilizumab therapy, as well as the drug survival rate for three years, were not inferior in elderly RA compared to young RA patients.